PENGEMBANGAN EKONOMI BERBASIS POTENSI LOKAL DI DESA KAMAIFUI KECAMATAN MATARU - Reni Sriyanti Besi; Paulus Malaimabi; Obetnego Kamalau; Daud Kafomai; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
The purpose of this study is to identify the potential natural resources for development in Kamaifui Village, Mataru District. The village has significant potential for developing a local resource-based economy (coffee, candlenut, and cocoa). Interviews were conducted in Kamaifui Village, Mataru District, on October 11, 2025. The results revealed: (1) the potential natural resources of Kamaifui Village, (2) ways to increase community capacity to develop the local economy, (3) what is being addressed in infrastructure development.